The emerging roles of leukocyte cell-derived chemotaxin-2 in immune diseases: From mechanisms to therapeutic potential - Zhu, Ming-Hui; Liu, Yan-Jun; Li, Chang-Yun; Tao, Fan; Yang, Guan-Jun; Chen, Jiong (Frontiers in Immunology, 2023)
Leukocyte cell-derived chemotaxin-2 (LECT2, also named ChM-II), initially identified as a chemokine mediating neutrophil migration, is a multifunctional secreted factor involved in diverse physiological and pathological processes. The high sequence similarity of LECT2 among different vertebrates makes it possible to explore its functions using comparative biology. LECT2 is associated with many immune processes and immune-related diseases via binding to cell surface receptors such as CD209a, Tie1, and Met in various cell types. In addition, the misfolding LECT2 also lead to amyloidosis of several crucial tissues (kidney, liver, and lung, etc) via inducing formation of insoluble fibrils. However, the mechanisms of LECT2-mediated diverse immune pathogenic conditions in various tissues remain to be fully elucidated due to the functional and signaling heterogeneity. Here, we provide a comprehensive summary of the structure, the “double-edged sword” function, and the extensive signaling pathways of LECT2 in immune diseases, as well as the potential applications of LECT2 in therapeutic interventions in preclinical or clinical trials. This review will provide an integrated perspective on the current understanding of all LECT2 associated with immune diseases, with the aim of facilitating the development of drugs or probes against LECT2 for the theranostics of immune-related diseases.